Paramagnetic garnet-type transparent ceramics, magneto-optical materials and magneto-optical devices

CN118201890BActive Publication Date: 2026-10-23SHIN ETSU CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280074315.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2022-10-27
Publication Date
2026-10-23
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

如果费尔德常数变大,则能够缩短使入射光旋转45度所需的元件长,因此总的吸收量变少,但如果厚1.5mm下的直线透射率为35%,即使元件长成为一半,45度旋转厚度透射率也不到1%,离实用化还很远

Benefits of technology

[0054]根据本发明,能够提供真正透明的、光学均质性高的顺磁性石榴石型透明陶瓷,该陶瓷为含有铽和钇的顺磁性石榴石型氧化物。进而,由于热导率高,光学均质性也良好,因此可应用于输出100W以上的高输出激光装置,由于陶瓷烧结体,因此是放大容易的、真正实用的装置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118201890B_ABST
    Figure CN118201890B_ABST
Patent Text Reader

Abstract

Provided is a paramagnetic garnet-type transparent ceramic which is a sintered body of a composite oxide represented by the following formula (1), contains, as a sintering aid, SiO2 at more than 0 mass% and 0.1 mass% or less, has an average sintered particle diameter of 5 μm or more, has a total light transmittance of 84.0% or more at a wavelength of 1064 nm for an optical path length of 25 mm, and has a forward scattering of 0.5% or less, and further has a total light transmittance of 84.0% or more at a wavelength of 1300 nm for an optical path length of 25 mm, and has a forward scattering of 0.5% or less, the ceramic being truly transparent and having high optical homogeneity.(Tb 1‑x‑y Y x Sc y )3(Al 1‑z Sc z )5O 12 (1) (in the formula, 0.05 ≤ x ≤ 0.4, 0 ≤ y < 0.004, 0.6 ≤ 1 - x - y < 0.95, 0 ≤ z < 0.004, 0.001 < y + z < 0.005.)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to paramagnetic garnet-type transparent ceramics, and more specifically, to magneto-optical materials comprising terbium-containing garnet-type transparent ceramics suitable for constituting magneto-optical devices such as optical isolators, and to magneto-optical devices using such magneto-optical materials. Background Technology

[0002] In recent years, high output of fiber lasers has become achievable, leading to a significant increase in the popularity of laser processing equipment using these fiber lasers. However, when laser sources are assembled into laser processing equipment, the resonant state becomes unstable and oscillations become disordered if light is incident from an external source. This is especially true if the oscillating light is reflected back to the source by an optical system along its path, further disrupting the oscillation. To prevent this, an optical isolator is typically placed between the laser source and the fiber optic cable on the light-emitting side of the source.

[0003] The optical isolator includes a Faraday rotor, a polarizer disposed on the light incident side of the Faraday rotor, and an analyzer disposed on the light emitting side of the Faraday rotor. The Faraday rotor is utilized by applying a magnetic field parallel to the light's direction of travel. In this case, the polarized wave component of the light rotates only in a certain direction, regardless of whether it advances or retreats within the Faraday rotor. Furthermore, the Faraday rotor is adjusted to a length where the polarized wave component of the light rotates exactly 45 degrees. Here, if the polarization planes of the polarizer and analyzer are offset by 45 degrees in the direction of rotation of the advancing light, the polarized wave of the advancing light coincides with the positions of the polarizer and analyzer, thus allowing transmission. On the other hand, the polarized wave of the retreating light rotates in the opposite direction of the offset angle of the polarization plane of the polarizer, which is offset by 45 degrees from the analyzer position, by 45 degrees. Therefore, the polarization plane of the returning light at the polarizer position is offset by 45 degrees - (-45 degrees) = 90 degrees relative to the polarization plane of the polarizer, and cannot pass through the polarizer. This functions as an optical isolator that allows forward light to pass through and exit while blocking backward returning light.

[0004] Among the materials used to construct the Faraday rotor of the aforementioned optical isolator, TGG crystal (Tb3Ga5O) is currently known. 12 ) and TSAG crystal ((Tb (3-x) Sc x )Sc2Al3O 12 (Japanese Patent Application Publication No. 2011-213552 (Patent Document 1), Japanese Patent Application Publication No. 2002-293693 (Patent Document 2)). TGG crystals are widely used as standard crystals in fiber laser devices. On the other hand, TSAG crystals are said to have a Feld constant that is about 1.3 times that of TGG crystals, and they are materials that can be used in fiber laser devices. However, Sc is an extremely expensive raw material, so it has not yet been adopted from the perspective of manufacturing cost.

[0005] Subsequently, as in Japanese Patent No. 5611329 (Patent Document 3) and Japanese Patent No. 5935764 (Patent Document 4), TSAG crystals continued to be developed, but none of them achieved a reduction in the amount of Sc used, and they have not yet become widespread.

[0006] In addition to the above, TAG crystals (Tb3Al5O4) are also known as Faraday rotors with a larger Feld constant than TSAG. 12 However, because TAG crystals are decomposition-melting type crystals, they are limited by the fact that at the solid-liquid interface, the perovskite phase is formed first, followed by the TAG phase. That is, TAG crystals can only be grown in a state where the garnet and perovskite phases are mixed together, and it has not been possible to grow high-quality, large-sized TAG crystals.

[0007] In Japanese Patent No. 3642063 (Patent Document 5) and Japanese Patent No. 4107292 (Patent Document 6), the following method was proposed as a means to suppress this mixed crystal: by making the polycrystalline raw material rod or seed crystal used for FZ cultivation porous, the perovskite phase, as the primary phase, preferentially precipitates in the porous medium. However, in reality, as the melting position moves, the position where the perovskite phase is more likely to precipitate also moves. Therefore, although only the interface between the seed crystal and the polycrystalline raw material rod is made porous, it is essentially impossible to completely suppress the precipitation of the perovskite phase.

[0008] Given these limitations, Japanese Patent Application Publication No. 2008-7385 (Patent Document 7) proposes a material made of ceramic containing an oxide of TAG that is translucent. Ceramic can be sintered at temperatures 100°C or higher below its melting point, thus solving the problem of decomposition and melting that is a concern in single-crystal cultivation. In fact, TAG decomposition begins above 1840°C; therefore, as long as it can be sintered densely below this temperature to just reach the theoretical density, a transparent sintered body of TAG single phase can be obtained.

[0009] Patent document 7 discloses a method for manufacturing ceramics containing terbium-aluminum oxide with a garnet structure. This method includes a raw material preparation step, a pre-firing step, a pre-firing powder pulverization step, a molding step, and a firing step. Specifically, if the average particle size of the pulverized pre-firing powder is 0.2–1.6 μm in the pre-firing powder pulverization step, and the density after molding in the molding step is 3.26 g / cm³, then... 3 The above methods enable the manufacture of TAG ceramics with high light transmittance.

[0010] However, in Patent Document 7, its light transmittance is extremely insufficient; even at a thickness of 1.5 mm, the linear transmittance is at most 35%. Incidentally, when using TAG as a Faraday element in optical isolators, for example, in the case of a 1.06 μm wavelength laser, the element length required to rotate the light by 45 degrees would be approximately 15 mm, roughly 10 times the length in this document. For a material that transmits only 35% of light at a thickness of 1.5 mm, if the element length is increased tenfold, the transmittance would be less than 0.01%, essentially zero, rendering it completely ineffective.

[0011] That is, even for ceramic manufacturing methods that can suppress heterogeneous phase formation, practical TAG (Transformation and Grafting) is not yet available.

[0012] It should be noted that Patent Document 6 shows that if a portion of the Tb in the TAG crystal is replaced with Ce, the Feld constant becomes larger compared to TAG. While a larger Feld constant allows for a shorter element length required to rotate the incident light 45 degrees, thus reducing the overall absorption, if the linear transmittance at a thickness of 1.5 mm is 35%, even with half the element length, the transmittance at a 45-degree rotation is still less than 1%, far from practical application.

[0013] In the aforementioned situation, recently, a composition of (Tb) was disclosed. x Y 1-x )3Al5O 12 The dense ceramic sintered body with x = 0.5–1.0 exhibits a higher extinction ratio (improved from the existing 35 dB to over 39.5 dB) compared to existing TGG crystals, and also reduces insertion loss (improved from the existing 0.05 dB to 0.01–0.05 dB) (Yan Lin Aung, Akio Ikesue, Development of optical grade (Tb x Y 1-x )3Al5O 12 Ceramics as Faraday Rotator Material, J. Am. Ceram. Soc., (2017), 100(9), 4081-4087 (Non-Patent Document 1). The material disclosed in Non-Patent Document 1 is primarily ceramic, thus eliminating the perovskite heterogeneous phase precipitation that is problematic in TGG crystals. Furthermore, by replacing a portion of the Tb ions with Y ions, further loss reduction can be achieved, making it a material capable of producing extremely high-quality garnet-type Faraday rotors.

[0014] In addition, recently, international publication No. 2018 / 193848 (Patent Document 8) disclosed a paramagnetic garnet-type transparent ceramic, characterized in that it is a sintered body of a composite oxide represented by the following formula (1), and has a linear transmittance of 83% or more at a wavelength of 1064 nm with an optical path length of 15 mm.

[0015] (Tb 1-x-y Sc x Ce y )3(Al 1-z Sc z )5O 12 (1)

[0016] (In the formula, 0 < x < 0.08, 0 ≤ y ≤ 0.01, and 0.004 < z < 0.16.)

[0017] In Patent Document 8, improvements were made to achieve a Feld constant comparable to that of TAG and ensured a linear transmittance of over 83% with an optical path length of 15 mm, thus essentially reaching a practical level.

[0018] Existing technical documents

[0019] Patent documents

[0020] Patent Document 1: Japanese Patent Application Publication No. 2011-213552

[0021] Patent Document 2: Japanese Patent Application Publication No. 2002-293693

[0022] Patent Document 3: Japanese Patent No. 5611329

[0023] Patent Document 4: Japanese Patent No. 5935764

[0024] Patent Document 5: Japanese Patent No. 3642063

[0025] Patent Document 6: Japanese Patent No. 4107292

[0026] Patent Document 7: Japanese Patent Application Publication No. 2008-7385

[0027] Patent Document 8: International Publication No. 2018 / 193848

[0028] Non-Patent Literature 1: Yan Lin Aung, Akio Ikesue, Development of optical grade (TbxY1-x)3Al5O12 ceramics as Faraday rotator material, J.Am.Ceram.Soc., (2017), 100(9), 4081-4087 Summary of the Invention

[0029] The problem that the invention aims to solve

[0030] However, the inventors actually tried to experiment again with the material in non-patent document 1, and then, with very little reproducibility, confirmed that it was almost impossible to obtain a high-quality ceramic sintered body with a small insertion loss compared to TGG crystals.

[0031] Furthermore, regarding the sample of the material that reproduces the embodiment of Patent Document 8, the inventors adjusted a laser with an actual wavelength of 1064 nm to a beam diameter of 1.6 mm and attempted to incident it with an output power of 100 W. The results showed that the change in the incident laser beam diameter due to thermal lensing exceeded 15%. Since the change in beam diameter when a laser with a wavelength of 1064 nm and an incident power of 100 W is incident is preferably less than 10%, it is difficult to say that the material of Patent Document 8 truly possesses high-power applicability.

[0032] The present invention was made in view of the above-mentioned actual situation, and its purpose is to provide a truly transparent paramagnetic garnet-type transparent ceramic, a magneto-optical material, and a magneto-optical device using the same, comprising a sintered body containing paramagnetic garnet-type oxides of terbium and yttrium.

[0033] Methods for solving problems

[0034] In order to achieve the above objectives, the present invention provides the following paramagnetic garnet-type transparent ceramic, magneto-optical material, and magneto-optical device. 1.

[0036] A paramagnetic garnet-type transparent ceramic, which is a sintered body of a composite oxide represented by the following formula (1), is characterized in that, as a sintering aid, it contains more than 0.1% by mass and less than 0.1% by mass of SiO2, has an average sintered particle size of 5 μm or more, a total light transmittance of 84.0% or more at a wavelength of 1064 nm with an optical path length of 25 mm, and forward scattering of 0.5% or less, and a total light transmittance of 84.0% or more at a wavelength of 1300 nm with an optical path length of 25 mm, and forward scattering of 0.5% or less.

[0037] (Tb 1-x-y Y x Scy )3(Al 1-z Sc z )5O 12 (1)

[0038] In the formula, 0.05≤x≤0.4, 0≤y<0.004, 0.6≤1-xy<0.95, 0≤z<0.004, and 0.001<y+z<0.005. 2.

[0040] According to the paramagnetic garnet-type transparent ceramic of 1, the Feld constant at a wavelength of 1064 nm is above 32 rad / (T·m). 3.

[0042] According to 1 or 2, the paramagnetic garnet-type transparent ceramic has an extinction ratio of 42dB or higher within the optically effective diameter of the entire surface when a laser with a wavelength of 1064nm is incident with an optical path length of 25mm. 4.

[0044] According to any one of 1 to 3, the paramagnetic garnet-type transparent ceramic wherein the change in the beam diameter when a laser with a wavelength of 1064 nm is incident with a beam diameter of 1.6 mm and an incident power of 100 W and an optical path length of 25 mm is 10% or less. 5.

[0046] The paramagnetic garnet-type transparent ceramic according to any one of 1 to 4 has a thermal conductivity of 4.8 W / (m·K) or higher. 6.

[0048] Magneto-optical materials comprising any one of paramagnetic garnet-type transparent ceramics according to any one of 1 to 5. 7.

[0050] A magneto-optical device, which is constructed using the magneto-optical material described in 6. 8.

[0052] According to the magneto-optical device described in 7, which includes the paramagnetic garnet-type transparent ceramic as a Faraday rotor, the magneto-optical device is an optical isolator that can be used in the wavelength range of 0.9 μm and below 1.1 μm, with polarizing materials on the front and back of the optical axis of the Faraday rotor.

[0053] The effects of the invention

[0054] According to the present invention, a truly transparent paramagnetic garnet-type transparent ceramic with high optical homogeneity can be provided, wherein the ceramic is a paramagnetic garnet-type oxide containing terbium and yttrium. Furthermore, due to its high thermal conductivity and good optical homogeneity, it can be applied to high-output laser devices with an output of 100W or more, and because it is a sintered ceramic body, it is an easily scaled-up and truly practical device. Attached Figure Description

[0055] Figure 1 This is a cross-sectional schematic diagram illustrating an example of a configuration of an optical isolator using the magneto-optical material of the present invention as a Faraday rotor. Detailed Implementation

[0056] <Paramagnetic Garnet-type Transparent Ceramics>

[0057] The following describes the paramagnetic garnet-type transparent ceramics involved in this invention.

[0058] The transparent ceramic material involved in this invention is a paramagnetic garnet-type transparent ceramic, which is a sintered body of a composite oxide represented by the following formula (1). It is characterized in that, as a sintering aid, it contains more than 0% by mass and less than 0.1% by mass of SiO2, has an average sintered particle size of more than 5 μm, a total light transmittance of more than 84.0% at a wavelength of 1064 nm with an optical path length of 25 mm, and forward scattering of less than 0.5%, and a total light transmittance of more than 84.0% at a wavelength of 1300 nm with an optical path length of 25 mm, and forward scattering of less than 0.5%.

[0059] (Tb 1-x-y Y x Sc y )3(Al 1-z Sc z )5O 12 (1)

[0060] (In the formula, 0.05≤x≤0.4, 0≤y<0.004, 0.6≤1-xy<0.95, 0≤z<0.004, 0.001<y+z<0.005.)

[0061] In Equation (1), terbium (Tb) is the material with the largest Feld constant among paramagnetic elements excluding iron (Fe), especially when contained in oxides with garnet structures. It is completely transparent at a wavelength of 1064 nm, and is therefore the most suitable element for use in optical isolators in this wavelength range.

[0062] Yttrium (Y) has an ionic radius approximately 2% smaller than that of terbium. When combined with aluminum to form a composite oxide, it is a material capable of stably forming a garnet phase compared to the perovskite phase and reducing residual strain in the crystallites. This prevents scattering caused by heterogeneous phases, extinction ratio degradation due to internal stress, and absorption by terbium ion ff transitions. Therefore, it is an important constituent element in this invention. Furthermore, by replacing a portion of the terbium ions with yttrium ions, the sinterability (combination reactions during heating, rapid phase changes, and the accompanying rapid changes in specific gravity) is averaged out. Therefore, compared to the case without yttrium ion replacement, the amount of residual porosity in the ceramic sintered body can be effectively limited. Thus, it is a preferred constituent element in this invention.

[0063] Aluminum (Al) is the material with the smallest ionic radius among trivalent ions that can stably exist in oxides with a garnet structure, and it is the element that minimizes the lattice constant of paramagnetic garnet-type oxides containing terbium. If the lattice constant of the garnet structure can be reduced without changing the terbium content, the Feld constant per unit length can be increased, which is therefore preferred. The Feld constant of actual TAG is increased to 1.25 to 1.5 times that of TGG. Therefore, even when reducing the relative concentration of terbium by replacing a portion of the terbium ions with yttrium ions, the Feld constant per unit length can be kept at a level equal to or slightly lower than that of TGG, making it a preferred constituent element in this invention.

[0064] Scandium (Sc) is a material with an intermediate ionic radius that can be solid-dissolved in oxides with a garnet structure at sites of both terbium and a portion of aluminum. When the proportions of rare earth elements containing terbium and yttrium with aluminum deviate from the stoichiometric ratio due to weighing errors, Scandium acts as a buffer material to precisely match the stoichiometric ratio, thereby minimizing the formation energy of microcrystals and adjusting the distribution ratio of terbium and yttrium-containing rare earth sites to aluminum sites. Furthermore, Scandium is an element that effectively suppresses the precipitation of both alumina-type and perovskite-type heterogeneous phases, making it indispensable in this invention.

[0065] However, since scandium can be easily dissolved at both terbium and aluminum sites, if the amount added is easily increased, i.e., if the proportion of scandium in the mixed raw materials is significantly increased, the effect of scandium concentration inhomogeneity cannot be ignored. This results in sintered particle aggregates in the sintered body after the sintering process, where each sintered particle has different amounts of scandium dissolved at the terbium and aluminum sites respectively. As a result, there are problems not only (i) deviations in the effective refractive index of each sintered particle and deterioration of forward scattering caused by overall refractive index inhomogeneity in the sintered body, but also (ii) scandium has an excessive sintering inhibition effect, thus the sintered body aggregates into large particle sizes, thereby hindering the homogenization process. Consequently, the grain boundary surface area can hardly be reduced, resulting in the retention of strain and subtle interface scattering within the sintered body, leading to a local decrease in extinction ratio, a local decrease in thermal conductivity (local reduction), and consequently a decrease in average thermal conductivity (average thermal conductivity). In this case, for example, if there is a local decrease in thermal conductivity, the change in the beam diameter when a 100W laser is incident increases to more than 15%, which is therefore not preferred.

[0066] Due to the contradictory nature of the above, regarding the amount of scandium added, it is preferable to find the smallest possible range while maintaining the effect of suppressing heterogeneous precipitation, and manage it within that range.

[0067] In equation (1), x is in the range of 0.05 ≤ x ≤ 0.4, preferably 0.06 ≤ x ≤ 0.3995, and more preferably 0.1 ≤ x ≤ 0.399. If x is in this range, the perovskite-type heterogeneous phase can be reduced to a level that is undetectable by X-ray diffraction (XRD) analysis.

[0068] When x is less than 0.05, the effect of partially replacing terbium with yttrium is not achieved, and the conditions are essentially no different from those for manufacturing TAG. Therefore, it is difficult to stably manufacture high-quality ceramic sintered bodies with low scattering and low absorption, which is not preferred. Furthermore, when x is greater than 0.4, the Feld constant for the 1064nm wavelength becomes less than 32 rad / (T·m), which is also not preferred. Moreover, if the relative concentration of terbium is excessively reduced, the total length required to rotate the 1064nm laser by 45 degrees becomes longer, exceeding 25mm, making manufacturing difficult, which is also not preferred.

[0069] In equation (1), the range of y is 0 ≤ y < 0.004, preferably 0.0005 ≤ y < 0.004, and more preferably 0.001 ≤ y < 0.004. If y is within this range, the perovskite-type heterogeneous phase can be reduced to a level that cannot be detected by X-ray diffraction (XRD) analysis, which is therefore preferred. Furthermore, it is also preferred because it can prevent an excessive decrease in thermal conductivity caused by homogeneity and grain boundary scattering of the sintered body.

[0070] When y is 0.004 or higher, the precipitation suppression effect of perovskite-type heterogeneous phase or alumina heterogeneous phase becomes saturated and no longer changes. This results in sintering inhomogeneity, residual sintering strain, or residual grain boundary scattering caused by the excessive effect of scandium's sintering suppression. As a result, there is a local decrease in extinction ratio and a decrease in the average thermal conductivity, which is therefore not preferred.

[0071] In equation (1), the range of 1-xy is 0.6 ≤ 1-xy < 0.95, more preferably 0.6 ≤ 1-xy < 0.899. If 1-xy is in this range, a large Feld constant can be ensured, while high transparency can be obtained at a wavelength of 1064 nm.

[0072] In formula (1), the range of z is 0 ≤ z < 0.004, more preferably 0.0005 ≤ z < 0.004, and even more preferably 0.001 ≤ z < 0.004. If z is within this range, the perovskite-type heterogeneous phase can be reduced to a level that cannot be detected by X-ray diffraction (XRD) analysis, which is therefore preferred. Furthermore, it can also prevent excessive reduction in thermal conductivity caused by homogeneity and grain boundary scattering of the sintered body, which is also preferred.

[0073] When z is 0.004 or higher, the precipitation suppression effect of perovskite-type heterogeneous phase or alumina heterogeneous phase becomes saturated and no longer changes. This results in sintering inhomogeneity, residual sintering strain, or residual grain boundary scattering caused by the excessive effect of scandium's sintering suppression. As a result, there is a local decrease in extinction ratio and a decrease in the average thermal conductivity, which is therefore not preferred.

[0074] In formula (1), the range of y+z is 0.001 < y+z < 0.005, more preferably 0.0015 < y+z < 0.005, and even more preferably 0.002 < z < 0.005. If y+z is within this range, the perovskite-type heterogeneous phase can be reduced to a level that cannot be detected by X-ray diffraction (XRD) analysis, which is therefore preferred. Furthermore, it can also prevent excessive reduction in thermal conductivity caused by homogeneity and grain boundary scattering of the sintered body, which is also preferred.

[0075] When y+z is below 0.001, the risk of precipitation of perovskite-type heterogeneous phases and alumina-type heterogeneous phases increases, so it is not preferred. Furthermore, when y+z is above 0.005, the precipitation suppression effect of perovskite-type heterogeneous phases or alumina-type heterogeneous phases becomes saturated and no longer changes, resulting in sintering inhomogeneity, residual sintering strain, or residual grain boundary scattering caused by excessive sintering suppression effect of scandium. This results in a localized decrease in extinction ratio and a decrease in the average thermal conductivity, so it is also not preferred.

[0076] The paramagnetic garnet-type transparent ceramic of the present invention contains a composite oxide represented by the above formula (1) as the main component, and SiO2, which acts as a sintering aid, as a secondary component, limited to 0.1% by mass. If a trace amount of SiO2 is added as a sintering aid, the precipitation of perovskite-type heterogeneous phases, alumina-type heterogeneous phases, etc., is suppressed, thereby further improving the transparency of the paramagnetic garnet-type transparent ceramic. Furthermore, the trace amount of SiO2 vitrifies during sintering at 1400°C or higher, resulting in a liquid-phase sintering effect, which can promote the densification of the garnet-type ceramic sintered body. However, if more than 0.1% by mass of SiO2 is added, the change in the beam diameter of the 100W laser line with an incident length (optical path length) of 25mm and a wavelength of 1064nm and a beam diameter of 1.6mm exceeds 10%, which is not preferred.

[0077] The phrase "containing... as a main component" means containing 90% by mass or more of the composite oxide represented by the above formula (1). The content of the composite oxide represented by formula (1) is preferably 99% by mass or more, more preferably 99.9% by mass or more, even more preferably 99.99% by mass or more, and particularly preferably 99.999% by mass or more.

[0078] The paramagnetic garnet-type transparent ceramic of the present invention is composed of the aforementioned main components and secondary components, and may further contain other elements. Typical examples of other elements include rare earth elements such as lutetium (Lu) and cerium (Ce), or as various impurity groups (unavoidable components) such as sodium (Na), calcium (Ca), magnesium (Mg), phosphorus (P), tungsten (W), and molybdenum (Mo).

[0079] Regarding the content of other elements, when the total amount of Tb and Y is set to 100 parts by mass, it is preferably 10 parts by mass or less, more preferably 0.1 parts by mass or less, and particularly preferably 0.001 parts by mass or less (essentially zero).

[0080] The average sintered particle size of the paramagnetic garnet-type transparent ceramic of the present invention is 5 μm or more, preferably 5.5 μm or more. There is no particular upper limit on the average sintered particle size of the paramagnetic garnet-type transparent ceramic of the present invention, and it is typically 30 μm or less. If the average sintered particle size is less than 5 μm, the risk of thermal conductivity being lower than 4.8 W / (m·K) increases.

[0081] It should be noted that the average sintered grain size of the paramagnetic garnet-type transparent ceramics mentioned here refers to the average grain size of the crystals in the secondary sintered body after HIP treatment in the manufacturing method described later. This can be determined by directly observing the polished surface using a microscope, etc. As an example, the reflected electron image of an electron microscope (SEM) can be cited. If it is difficult to determine the grain size on the polished surface, hot etching at 1200-1300℃ and treatment with 0.1M dilute hydrochloric acid can be performed to make the grain boundaries obvious. Regarding the crystal grain size (grain size), let the length of an arbitrarily drawn line in a high-resolution image such as SEM be C, the number of particles on the line be N, and the image magnification be M. The following formula can be used to calculate it ("Lineal Intercept Technique for Measuring Grain Size in Two-Phase Polycrystalline Ceramics" Journal of the American Ceramic Society, 55, 109 (1972)).

[0082] D = 1.56C / (MN)

[0083] In this case, N is preferably 10 or more, and more preferably 100 or more.

[0084] The paramagnetic garnet-type transparent ceramic of the present invention exhibits a colorless and transparent appearance. Its total light transmittance at a wavelength of 1064 nm with an optical path length of 25 mm is 84.0% or more, and its forward scattering is 0.5% or less. Furthermore, its total light transmittance at a wavelength of 1300 nm with an optical path length of 25 mm is 84.0% or more, and its forward scattering is 0.5% or less. If the paramagnetic garnet-type transparent ceramic of the present invention not only has high transmittance at the intended wavelength (1064 nm), but also has the same value as the wavelength of 1064 nm in a longer wavelength range, with a total light transmittance of 84.0% or more and forward scattering of 0.5% or less, then the extinction ratio is improved. When a 100W laser line with a wavelength of 1064 nm and a beam diameter of 1.6 mm is incident with an optical path length of 25 mm, the change in the beam diameter is 10% or less, and the thermal conductivity is 4.8 W / (m·K) or more, which is therefore preferable.

[0085] It should be noted that in this invention, "total light transmittance" refers to the ratio of the intensity of light transmitted through a transparent ceramic sample to the intensity of light at the same wavelength as the object wavelength when the integrated sphere transmittance spectrum (light intensity) is set to 100% in a blank (space) state without a sample in the measurement optical path. That is, when the intensity of light at the object wavelength (incident light intensity) measured in the blank state is set to I0, and the intensity of light collected by the integrated sphere, including scattered light, after passing through the transparent ceramic sample is set to I, it can be expressed as I / I0×100 (%) (the same applies in the embodiments below). Furthermore, "forward scattering" is defined as follows: After measuring the above-mentioned "total light transmittance" with a sample placed in the measurement optical path, the exit window located at the opposite end of the incident window of the integrated sphere is opened. Light is then incident on the sample again in this state. Of the light emitted from the sample, only the unscattered, straight transmitted light escapes out of the integrating sphere. Only the intensity I of the light that is slightly scattered within the transparent ceramic sample and incident at an angle within the integrating sphere is received and measured. S Therefore, using the I0 from before, we can use I... S The light intensity represented by ( / I0×100(%) is the "forward scattering" of the sample (the same applies below in the examples).

[0086] Regarding the paramagnetic garnet-type transparent ceramic of the present invention, the Field constant at a wavelength of 1064 nm is preferably 32 rad / (T·m) or higher, more preferably 36 rad / (T·m) or higher. If the Field constant is 32 rad / (T·m) or higher, it is possible to replace the isolator with an isolator using TGG single crystal without increasing the overall size of the isolator through the design and research of the outer cylinder magnet. If the Field constant is 36 rad / (T·m) or higher, it is possible to easily replace the existing TGG single crystal without changing the component design.

[0087] Regarding the paramagnetic garnet-type transparent ceramic of the present invention, as a Faraday rotor (a separate ceramic element), the extinction ratio at a wavelength of 1064 nm with an optical path length of 25 mm is preferably 42 dB or more. In particular, the extinction ratio of the entire surface within the optically effective diameter at which a laser with a wavelength of 1064 nm is incident with an optical path length of 25 mm is preferably 42 dB or more, more preferably 44 dB or more, and even more preferably 45 dB or more. If the garnet composition is within the range of the present invention, local strain is reduced, and excessive grain growth suppression does not occur. Therefore, a transparent ceramic sintered body with overall homogeneity and low grain boundary scattering on the optically effective surface is formed. Thus, as a Faraday rotor (a separate ceramic element), the extinction ratio of the entire surface within the optically effective diameter at a wavelength of 1064 nm with an optical path length of 25 mm can be stably managed to be 42 dB or more.

[0088] It should be noted that the "extinction ratio" referred to here is the polarization of a 10-20mW laser with a wavelength of 1064nm, with its beam diameter expanded to the diameter of the entire optical surface of the object's paramagnetic garnet-type transparent ceramic, from 0 to 90 degrees. The laser is incident perpendicularly (in the optically utilized axial direction) to the optical surface of the object's paramagnetic garnet-type transparent ceramic, and the emitted light passes through a polarizer and enters a photodetector. The intensity of the light is measured by the photodetector, and the value is calculated from the maximum value (I0') and the minimum value (I') according to the following formula (the same applies in the following examples).

[0089] Extinction ratio (dB / 25mm) = -10 × log 10 (I' / I0')

[0090] Furthermore, the term "optically effective diameter" refers to the optically effective region (optically effective area) within the optical surface of a transparent ceramic. Specifically, in the case of a cylindrical paramagnetic garnet-type transparent ceramic, it refers to the region within the optical surface (circular surface) located on its optically usable axis, excluding the optically unusable outer edge portion. Expressed as the area ratio of the optical surface, it refers to the region excluding the area equivalent to 10% of the outer edge portion of the optical surface; that is, it refers to the region with an area ratio of 90% extending from the outer edge of the optical surface to the inner side. Additionally, the term "optically effective area" means the region within the paramagnetic garnet-type transparent ceramic that effectively functions as a magneto-optical material when incident light is transmitted and emitted.

[0091] Furthermore, regarding the paramagnetic garnet-type transparent ceramic of the present invention, the change in beam diameter when a 1064nm laser with a beam diameter of 1.6mm and an incident power of 100W is incident with an optical path length of 25mm is preferably 10% or less, more preferably 9% or less, and even more preferably 8% or less. If the change in beam diameter is 10% or less, the energy density of the processing point for marking, scribing, and other precision machining is within the specified range, thus it can be used in a high-power laser system of 100W.

[0092] The aforementioned "change in beam diameter" is calculated as follows.

[0093] That is, the beam diameter of the incident light (1064nm wavelength, 100W output power, 1.6mm diameter collimated laser light) is measured using a beam analyzer when it is incident on the optical surface of the object's paramagnetic garnet-type transparent ceramic. This value is set as r0. Next, the beam diameter of the transmitted light (25mm long paramagnetic garnet-type transparent ceramic) is measured and set as r. The value calculated by (1-r / r0)×100 (%) is taken as the change in beam diameter. It should be noted that since the change in beam diameter varies with the setting position and angle of the object's paramagnetic garnet-type transparent ceramic in the measurement system, as well as daytime errors, the setting position and angle of the object's paramagnetic garnet-type transparent ceramic in the measurement system can be changed during the measurement, or the measurement can be performed several times (at least twice) by changing the day of measurement. The maximum value of the measured value is taken as the change in beam diameter.

[0094] The thermal conductivity of the paramagnetic garnet-type transparent ceramic of the present invention is preferably 4.8 W / (m·K) or higher. The thermal conductivity referred to here is the value measured using the laser flash method according to JIS R1611, and is the average thermal conductivity described above. However, the sample used for thermal conductivity evaluation using the laser flash method does not need to be finely machined to a length of 25 mm, which is intended for use as a magneto-optical material. A size of approximately 1 mm in thickness and φ of approximately 10 mm is sufficient for adequate thermal conductivity measurement. However, apart from changing only the shape of the molded body, it needs to be finely machined into a thermal conductivity evaluation sample that is entirely consistent with the manufacturing method of the paramagnetic garnet-type transparent ceramic for magneto-optical applications. By measuring this thermal conductivity evaluation sample, the thermal conductivity of the paramagnetic garnet-type transparent ceramic for magneto-optical applications can be obtained.

[0095] <Manufacturing Method of Paramagnetic Garnet-Type Transparent Ceramics>

[0096] [raw material]

[0097] As raw materials used in this invention, metal powders containing terbium, yttrium, scandium, and aluminum, or substances obtained by dissolving the aforementioned metal powders in aqueous solutions of nitric acid, sulfuric acid, uric acid, etc., or oxide powders of the aforementioned elements are preferably used. Furthermore, substances obtained by co-precipitating the aforementioned elements are preferably used as raw materials. The purity of the aforementioned raw materials is preferably 99.9% by mass or more, and particularly preferably 99.99% by mass or more.

[0098] By weighing a specified amount of these elements to form a composition corresponding to formula (1), and mixing them, a starting material can be manufactured. Alternatively, the mixed material weighed in the above manner can be sintered to obtain a sintered material with the desired cubic garnet-type oxide as the main component, and this sintered material can be pulverized into powder and used as a starting material. The sintering temperature is preferably 950°C or higher and lower than the subsequent sintering temperature, more preferably 1100°C or higher and lower than the subsequent sintering temperature. Here, "as the main component" means that the main peak obtained from the powder X-ray diffraction results of the sintered material includes diffraction peaks from the garnet structure. It should be noted that when the proportion of the perovskite-type heterogeneous phase and the alumina heterogeneous phase relative to the garnet parent phase is less than 1%, since even the main peaks of these powder X-ray diffraction patterns are almost undetectable, the obtained powder X-ray diffraction results are basically very similar to the single-phase garnet pattern.

[0099] There are no particular limitations on the shape of the starting material powder. For example, square, spherical, or plate-shaped powders are preferred. Furthermore, even powders that have undergone secondary agglomeration are preferred, as are granular powders granulated by spray drying or other granulation processes. Furthermore, there are no particular limitations on the preparation process of the starting material powder. Powders manufactured using co-precipitation, pulverization, spray pyrolysis, sol-gel methods, alkoxide hydrolysis, and all other synthetic methods are preferred. Additionally, the obtained powder can be appropriately processed using wet ball mills, bead mills, jet mills, dry jet mills, hammer mills, etc.

[0100] In the garnet-type oxide powder raw material used in this invention, various organic additives are sometimes added to improve the quality stability and yield in subsequent ceramic manufacturing processes. In this invention, there are no particular limitations on these additives. That is, various dispersants, binders, lubricants, plasticizers, etc., can be preferably used. However, as these organic additives, it is preferable to select high-purity types that do not contain unwanted metal ions.

[0101] [Manufacturing Process]

[0102] In this invention, using the aforementioned starting materials, after pressing into a predetermined shape, degreasing is performed, followed by sintering to produce a densified sintered body with a relative density of at least 94%. As a subsequent step, hot isostatic pressing (HIP) is preferably performed. It should be noted that if HIP is performed directly, the paramagnetic garnet-type transparent ceramic is reduced, resulting in some oxygen defects. Therefore, it is preferable to perform micro-oxidation HIP or annealing in an oxidizing atmosphere after HIP (oxidative annealing) to restore the oxygen defects. This allows for the acquisition of a transparent garnet-type oxide ceramic without defect absorption.

[0103] (forming)

[0104] In the manufacturing method of the present invention, conventional compression molding processes can be preferably utilized. Specifically, very common uniaxial pressing processes, such as filling a mold with pressure applied from a certain direction, cold isostatic pressing (CIP) processes where the molded body is sealed in a deformable waterproof container and pressurized by hydrostatic pressure, and warm isostatic pressing (WIP) processes, can be preferred. It should be noted that, regarding the applied pressure, there are no particular limitations as long as it is appropriately adjusted while confirming the relative density of the resulting molded body. For example, when managing a pressure range of approximately 300 MPa or less that can be handled by commercially available CIP or WIP devices, manufacturing costs can be suppressed. Alternatively, in addition to the molding process, hot pressing, spark plasma sintering, microwave heating, etc., which are performed in one continuous process to sintering, can also be preferred. Furthermore, it is also possible to manufacture the molded body using casting molding instead of compression molding. By optimizing the shape and size of the oxide powder used as the starting material and the combination of various organic additives, molding methods such as pressure casting, centrifugal casting, and extrusion molding can also be used.

[0105] (Defatted)

[0106] In the manufacturing method of the present invention, a conventional degreasing process can be preferably used. That is, a heating degreasing process using a furnace can be performed. Furthermore, there are no particular restrictions on the type of atmospheric gas used at this time, and air, oxygen, hydrogen, etc. can be preferably used. There are also no particular restrictions on the degreasing temperature, but when using raw materials mixed with organic additives, it is preferable to heat the mixture to a temperature that can decompose and remove the organic components.

[0107] (sintering)

[0108] In the manufacturing method of the present invention, a conventional sintering process can be preferably used. That is, a heating sintering process using resistance heating, induction heating, or similar methods can be preferred. There are no particular limitations on the atmosphere at this time; various atmospheres such as inert gases, oxygen, hydrogen, and helium can be used, or sintering can be performed under reduced pressure (vacuum). However, it is preferable to prevent oxygen loss in the final sintered body; therefore, oxygen or a reduced-pressure oxygen atmosphere is preferred.

[0109] The sintering temperature in the sintering process is preferably 1500–1780°C, and particularly preferably 1550–1750°C. If the sintering temperature is within this range, heterogeneous phase precipitation is suppressed while densification is promoted, and therefore it is preferred.

[0110] A sintering holding time of several hours is sufficient in the sintering process, but the relative density of the sintered body must be at least 94%. Furthermore, if the holding time is longer than 10 hours to achieve a relative density of 99% or higher for the sintered body, the final transparency will be improved, which is therefore preferred.

[0111] (Hot Isostatic Pressing (HIP))

[0112] In the manufacturing method of the present invention, after the sintering process, an additional hot isostatic pressing (HIP) process can be added.

[0113] It should be noted that, regarding the type of pressurized gas medium, inert gases such as argon and nitrogen, or Ar-O2, are preferred. The pressure applied using the pressurized gas medium is preferably 50–300 MPa, more preferably 100–300 MPa. If the pressure is less than 50 MPa, the improvement in transparency may not be achieved; if it exceeds 300 MPa, even increasing the pressure will not result in the same level of transparency improvement, placing excessive load on the device and potentially damaging it. For the applied pressure, a pressure of 196 MPa or less, which can be handled by commercially available HIP devices, is simple and preferred.

[0114] Furthermore, the processing temperature (specified holding temperature) is set within the range of 1100–1780°C, preferably 1200–1730°C. If the heat treatment temperature exceeds 1780°C, the risk of oxygen deficiency increases, which is therefore undesirable. Additionally, if the heat treatment temperature is below 1100°C, the improvement in transparency of the sintered body is almost impossible to achieve. It should be noted that there is no particular limitation on the holding time at the heat treatment temperature; however, if it is held for too long, the risk of oxygen deficiency increases, which is also undesirable. Typically, a range of 1–3 hours is preferred.

[0115] It should be noted that there are no particular limitations on the heater material, insulation material, and processing container for HIP treatment. Graphite, or molybdenum (Mo), tungsten (W), or platinum (Pt) can be preferred as the processing container, and yttrium oxide or gadolinium oxide can also be preferred. Especially when the treatment temperature is below 1500°C, platinum (Pt) can be used as the heater material, insulation material, and processing container, and the pressurized gas medium can be Ar-O2, thus preventing oxygen deficiency during HIP treatment, and is therefore preferred. When the treatment temperature exceeds 1500°C, graphite is preferred as the heater material and insulation material. However, in this case, any one of graphite, molybdenum (Mo), or tungsten (W) can be selected as the processing container, and further, as a double container inside, any one of yttrium oxide or gadolinium oxide can be selected. If an oxygen-releasing material is filled inside the container, the amount of oxygen deficiency during HIP treatment will be minimized, and is therefore preferred.

[0116] (Oxidative annealing)

[0117] In the manufacturing method of the present invention, after the HIP treatment is completed, oxygen deficiency sometimes occurs in the resulting transparent ceramic sintered body (HIP body), resulting in a faint gray appearance. In this case, it is preferable to perform an oxidation annealing treatment (oxygen deficiency recovery treatment) in an oxygen atmosphere at a temperature below the aforementioned HIP treatment temperature, typically 1000–1500°C, preferably above 1300°C and below 1500°C, more preferably 1350–1500°C, and even more preferably 1400–1500°C. There is no particular limitation on the holding time at this time, but it is preferable to select a time that is sufficient for the oxygen deficiency to be recovered without wasting electricity costs by performing a long treatment. Through this oxidation annealing treatment, even the transparent ceramic sintered body that faintly exhibits a gray appearance during the HIP treatment process can be made into a completely colorless, transparent, defect-free, paramagnetic garnet-type transparent ceramic.

[0118] (Optical Grinding)

[0119] In the manufacturing method of the present invention, it is preferable to optically grind the two end faces located on the optically usable axis of the paramagnetic garnet-type transparent ceramic that has undergone the above-described series of manufacturing processes. Regarding the optical surface accuracy at this time, λ / 2 or less is preferred, and particularly λ / 8 or less is particularly preferred when the measurement wavelength λ = 633 nm. It should be noted that by appropriately forming an antireflective coating on the optically ground surface, optical losses can be further reduced.

[0120] As described above, a paramagnetic garnet-type transparent ceramic can be provided, which is the paramagnetic garnet-type transparent ceramic of the present invention described above, that is, a sintered body containing a composite oxide of terbium and yttrium represented by the above formula (1), which, as a sintering aid, contains more than 0% by mass and less than 0.1% by mass of SiO2, has an average sintered particle size of 5 μm or more, a total light transmittance of 1064 nm at a length (optical path length) of 25 mm of 84.0% or more, and a forward scattering of less than 0.5%, and further, a total light transmittance of 1300 nm at a length (optical path length) of 25 mm of 84.0% or more, and a forward scattering of less than 0.5%. Furthermore, in the paramagnetic garnet-type transparent ceramic obtained in this way, preferably, the Feld constant for a wavelength of 1064 nm is 32 rad / (T·m) or more; preferably, the change in the beam diameter when a laser with a wavelength of 1064 nm is incident with a beam diameter of 1.6 mm and an incident power of 100 W and an optical path length of 25 mm is 10% or less; more preferably, the thermal conductivity is 4.8 W / (m·K) or more; and as a Faraday rotor (a separate ceramic element), preferably, the extinction ratio of the entire surface within the optically effective diameter when a laser with a wavelength of 1064 nm is incident with an optical path length of 25 mm is 42 dB or more.

[0121] [Magneoptic Devices]

[0122] Furthermore, since the paramagnetic garnet-type transparent ceramic of the present invention is envisioned as a magneto-optical material, it is preferable to apply a magnetic field parallel to its optical axis to the paramagnetic garnet-type transparent ceramic, and then set the polarizer and analyzer to have their optical axes offset from each other by 45 degrees, thereby constructing a magneto-optical device. That is, the magneto-optical material of the present invention is suitable for use in magneto-optical devices, and is particularly suitable for use as a Faraday rotor in an optical isolator with a wavelength of 0.9 to 1.1 μm.

[0123] Figure 1 This is a cross-sectional schematic diagram illustrating an example of an optical device, namely an optical isolator, having a Faraday rotor made of the magneto-optical material of the present invention as an optical element. Figure 1 In the optical isolator 100, a Faraday rotor 110 made of the magneto-optical material of the present invention is included. Before and after the Faraday rotor 110, a polarizer 120 and an analyzer 130, which are polarizing materials, are included. In addition, the optical isolator 100 is arranged in the order of polarizer 120, Faraday rotor 110, and analyzer 130, and preferably a magnet 140 is mounted on at least one of their sides.

[0124] Furthermore, the aforementioned optical isolator 100 is preferably used in industrial fiber laser devices. That is, it is suitable for preventing reflected light from the laser emitted from the laser source from returning to the light source, thereby preventing oscillations from becoming unstable.

[0125] Example

[0126] The following examples and comparative examples illustrate the present invention in more detail, but the present invention is not limited to the examples.

[0127] [Examples 1-7, Comparative Examples 1-6]

[0128] Terbium oxide powder, yttrium oxide powder, scandium oxide powder, and alumina powder manufactured by Shin-Etsu Chemical Industry Co., Ltd. were obtained. Furthermore, a liquid form of tetraethyl orthosilicate (TEOS) manufactured by Kishida Chemical Co., Ltd. was obtained. In terms of purity, all powder raw materials were 99.95% by mass or higher, and the liquid raw material was 99.999% by mass or higher.

[0129] Using the above raw materials, the mixing ratio was adjusted to produce 13 oxide raw materials with the final composition shown in Table 1.

[0130] That is, a mixed powder is prepared by weighing the terbium, yttrium, aluminum, and scandium in molar ratios as shown in Table 1. Then, TEOS is weighed so that its addition amount, converted to SiO2, is in the mass percentage of Table 1 and added to each raw material.

[0131] Then, while taking care to prevent cross-contamination, the mixture was dispersed and mixed in ethanol using an alumina ball mill for 15 hours. It was then spray-dried to produce granular raw materials with an average particle size of 20 μm.

[0132] Next, these powders were placed in a yttrium oxide crucible and calcined in a high-temperature muffle furnace at 1100°C for 3 hours to obtain calcined raw materials according to their respective compositions. The obtained calcined raw materials were subjected to X-ray diffraction (XRD) analysis using a powder X-ray diffraction apparatus manufactured by PANalytical. By comparing the reference data and the measured patterns of the X-ray diffraction patterns, the crystal system of the samples was determined. In almost all cases (for oxide raw materials No. 1–8 and 10–13), only peaks of the garnet single phase (cubic crystal) were detected. For oxide raw material No. 9, in addition to the peak pattern of the garnet phase, weak peaks of the perovskite heterogeneous phase were also detected.

[0133] The results are summarized in Table 1.

[0134] [Table 1]

[0135]

[0136] The resulting oxide raw materials were carefully dispersed and mixed again in ethanol using a nylon ball mill while taking precautions to prevent cross-contamination. The processing time was 24 hours for each mixture. Then, spray drying was performed to produce granular raw materials with an average particle size of 20 μm. The 13 powder raw materials were then subjected to uniaxial pressing and cold isostatic pressing at 198 MPa to obtain CIP (Compound In-Place) molded bodies. These molded bodies were then degreased in a muffle furnace at 1000°C for 2 hours. Next, the degreased molded bodies were placed in a vacuum sintering furnace and sintered at 1550°C for 3 hours to obtain 13 sintered bodies. At this point, the sintered relative density of the samples ranged from 94.5% to 98.8%.

[0137] The resulting sintered bodies were placed in a carbon heater-based HIP furnace and subjected to HIP treatment in an Ar atmosphere at 200 MPa, 1600 °C, and for 2 hours. The resulting sintered bodies showed almost no visible graying (oxygen deficiency absorption). However, as a precaution, each ceramic sintered body was subjected to batch-specific annealing in an oxygen atmosphere furnace at 1450 °C for 20 hours to fully restore oxygen deficiency. This resulted in 13 sintered bodies for the examples and comparative examples.

[0138] Next, each of the obtained ceramic sintered bodies was ground and polished to make it into a circular plate with a diameter of 10 mm and a thickness of 1 mm and a rod (cylindrical) with a diameter of 5 mm and a length of 25 mm. Then, the optical end faces of each sample were finally optically polished with an optical surface accuracy of λ / 8 (in the case of a measurement wavelength of λ = 633 nm).

[0139] In the samples obtained as described above, the thermal conductivity of the disc-shaped samples was measured according to the following procedure. Then, the samples were thermally etched, and the average sintered particle size of each sample was measured. Additionally, for the rod-shaped samples, the total light transmittance, forward scattering, and extinction ratio were measured as described below.

[0140] (Methods for determining thermal conductivity)

[0141] For the determination of thermal conductivity, the laser flash method was used according to JIS R1611. Specifically, for each sample with an outer diameter of 10 mm φ and a thickness of 1 mm, firstly, a differential scanning calorimeter manufactured by Perkin-Elmer was used to determine the specific heat by measuring the number n². Then, a thermal diffusivity measuring device manufactured by NETZSCH was used, with xenon lamp irradiation, to determine the thermal diffusivity by measuring the number n². Using these values ​​and the theoretical density of each component, the thermal conductivity was calculated according to the following formula.

[0142] Thermal conductivity (W / (m·K)) = Theoretical density (kg / m³)3 )"×"Specific heat capacity (J / (kg·K))"×"Thermal diffusivity (m)" 2 / s)”

[0143] (Method for determining the average sintered particle size)

[0144] The average sintered grain size of the sample was determined with reference to "Lineal Intercept Technique for Measuring Grain Size in Two-Phase Polycrystalline Ceramics," Journal of the American Ceramic Society, 55, 109 (1972). Specifically, it was determined by observing the grain boundaries of the optically etched end face of the final optically polished sample after being treated at 1300°C for 6 hours under atmospheric conditions using an optical microscope. With the average grain size set as D, the length of the arbitrarily drawn line set as C, the number of particles on the line set as N, and the image magnification set as M, the following formula was used...

[0145] D = 1.56C / (MN)

[0146] It is determined by two significant digits. It should be noted that N is approximately 10 to 20 in number.

[0147] (Methods for measuring total light transmittance and forward scattering)

[0148] For total light transmittance and forward scattering, a spectrophotometer V-670 manufactured by Nippon Spectrophotometer Co., Ltd. was used to measure two wavelengths: 1064 nm and 1300 nm. First, for the measurement of total light transmittance, light split by the spectrometer was irradiated onto the V-670 without a workpiece (sample) in place. The light was received by an integrating sphere pre-installed in the apparatus and a detector. The resulting illuminance was set as I0. Next, the workpiece was placed in the apparatus, and the split light was incident on the workpiece. The transmitted light was again collected by the integrating sphere and a detector. The resulting illuminance was set as I, and calculated using the following formula.

[0149] Total light transmittance (% / 25mm) = I / I0 × 100

[0150] Secondly, regarding the measurement of forward scattering, except for removing the reflector on the back of the integrating sphere from the aforementioned state where the workpiece is present, in the same measurement system, the spectral-split light is again incident on the workpiece, and the transmitted light is again collected by the integrating sphere and received by the detector. The obtained illuminance represents the scattered component other than the linearly transmitted component, and is denoted as I. S The following formula can be used to calculate it.

[0151] Forward scattering (% / 25mm) = I S / I0×100

[0152] It should be noted that the above-mentioned total light transmittance and forward scattering were measured for both wavelengths of 1064 nm and 1300 nm.

[0153] (Method for determining extinction ratio)

[0154] The extinction ratio of the Faraday rotor was measured as described below.

[0155] Regarding the extinction ratio, an optical system was constructed using a light source, collimating lens, polarizer, workpiece stage, analyzer, power meter, and Ge photodetector manufactured by NKT Photonics. The sample was illuminated with light of wavelength 1064 nm at a maximum beam diameter of 3 mmφ, allowing it to pass through the sample. The intensity I0' (maximum laser intensity) of the light was measured when the polarization plane of the analyzer was aligned with that of the polarizer. Then, the polarization plane of the analyzer was rotated 90 degrees, and the intensity I' (minimum laser intensity) was measured again when it was orthogonal to the polarizer's polarization plane. The result was then calculated based on the following formula.

[0156] Extinction ratio (dB / 25mm) = -10 × log 10 (I' / I0')

[0157] It should be noted that if the beam diameter is made larger than 3 mmφ, the edges of the beam will begin to be blocked on the outer periphery of a sample with a diameter of 5 mmφ. Therefore, the beam diameter of 3 mmφ is defined as the state of the entire surface within the actual optically effective diameter of the light incident on the sample.

[0158] Next, for the optically polished sample, an anti-reflective coating (AR coating) designed with a center wavelength of 1064 nm is applied.

[0159] For each ceramic sample obtained in this way, the changes in the Feld constant and the laser beam diameter caused by the thermal lens are measured as follows. That is, as... Figure 1As shown, polarizing elements (polarizer 120, analyzer 130) were placed before and after each obtained ceramic sample (equivalent to Faraday rotor 110). The ceramic sample was then inserted into the center of a neodymium-iron-boron magnet (magnet 140) with an outer diameter of 32 mm, an inner diameter of 6 mm, and a length of 40 mm. A high-power laser (beam diameter 1.6 mm) manufactured by IPG Photonics Japan Co., Ltd. was used to incident a high-power laser line with a wavelength of 1064 nm from both ends, and the Feld constant was measured. Furthermore, after removing the neodymium-iron-boron magnet, a high-power laser line with a wavelength of 1064 nm was incident on each ceramic sample under the same conditions as described above. The occurrence of thermal lensing was quantified and evaluated as a measure of the change in beam diameter.

[0160] (Method for determining the Feld constant)

[0161] The Feld constant V is calculated based on the following formula. It should be noted that the magnitude (H) of the magnetic field applied to the ceramic sample is a value calculated by simulation based on the dimensions of the measurement system, the remanent magnetic flux density (Br), and the coercivity (Hc) described above.

[0162] θ=V×H×L

[0163] (In the formula, θ is the Faraday rotation angle (rad), V is the Feld constant (rad / (T·m)), H is the magnitude of the magnetic field (T), and L is the length of the Faraday rotor (0.025m in this case).)

[0164] (Method for measuring the change in incident laser beam diameter caused by thermal lensing)

[0165] A high-power laser (1.6 mm beam diameter) manufactured by IPG Photonics Japan Co., Ltd. was used to emit a 100W spatially parallel beam. The beam diameter at the focal point was measured using a beam analyzer. Next, a ceramic sample was placed along the path of this emitted beam, and the change in beam diameter due to variations in sample placement was measured again using the beam analyzer. The difference between the two measurements was taken as the change in beam diameter caused by thermal lensing. It should be noted that this change in beam diameter is prone to measurement error; therefore, the same measurement was performed again on a later date, and the larger value was taken as the change in beam diameter.

[0166] The results are shown in Table 2.

[0167] [Table 2]

[0168]

[0169] Based on the above results, in all the examples (Examples 1-7) and Comparative Example 5, which are composed of the composite oxides of the present invention, the total light transmittance at wavelengths of 1064 nm and 1300 nm is 84.0% or higher, and the forward scattering is 0.5% or lower, resulting in an extinction ratio of 42 dB or higher. This confirms that highly transparent paramagnetic garnet-type transparent ceramics can be manufactured. Furthermore, the change in beam diameter caused by thermal lensing when a 100 W laser is incident is also suppressed to less than 10%, confirming that it can be mounted in a high-power laser system. However, in Comparative Example 5, the Tb concentration is excessively reduced, resulting in a Feld constant of less than 32 rad / (T·m). Furthermore, since the presence probabilities of Tb and Y are almost equal, and the average particle size is also smaller, the thermal conductivity remains at less than 4.8 W / (m·K).

[0170] Furthermore, in Comparative Examples 2-4, since no Sc was added, the extinction ratio, total light transmittance, forward scattering, and the change in beam diameter were all below the specified range. In the case of Comparative Example 1, due to the excessively high Tb ratio, the extinction ratio, total light transmittance, forward scattering, and the change in beam diameter caused by thermal lensing when a 100W output laser is incident were all below the specified range.

[0171] In Comparative Example 6, due to excessive SiO2 doping, the thermal conductivity, total light transmittance at a wavelength of 1300 nm, and the change in beam diameter caused by thermal lensing when a 100 W laser output is incident are all below the specified range.

[0172] It should be noted that, since the average sintered particle size of Examples 1 to 7 is 5 μm or more, the thermal conductivity of all of them is 4.8 W / (m·K) or more.

[0173] Based on the above results, by managing x, y, and z of equation (1) within the range specified in this invention, and by doping SiO2 within the specified range as a sintering aid, it is possible to provide a highly transparent paramagnetic garnet-type transparent ceramic with an average sintered particle size of 5 μm or more, a linear transmittance of 84.0% or more at a wavelength of 1064 nm with an optical path length of 25 mm, and a forward scattering of 0.5% or less; furthermore, a linear transmittance of 84.0% or more at a wavelength of 1300 nm with an optical path length of 25 mm, and a forward scattering of 0.5% or less. This results in a thermally... A paramagnetic garnet-type transparent ceramic with a conductivity of 4.8 W / (m·K) or higher, a Feld constant of 32 rad / (T·m) or higher at a wavelength of 1064 nm, and a beam diameter change of less than 10% caused by thermal lensing when a 100 W output laser with an optical path length of 25 mm and a wavelength of 1064 nm is incident, and an extinction ratio of 42 dB or higher at a wavelength of 1064 nm with an optical path length of 25 mm, can provide a high-performance magneto-optical device that can be used even for high-power applications when this transparent ceramic is used as a magneto-optical material.

[0174] It should be noted that the present invention has been described so far using the above-described embodiments, but the present invention is not limited to these embodiments. It can be modified in other embodiments, additions, changes, deletions, etc., within the scope that can be conceived by those skilled in the art. All solutions that can achieve the effects of the present invention are included within the scope of the present invention.

[0175] Explanation of reference numerals in the attached figures

[0176] 100 Optical Isolator

[0177] 110 Faraday Rotor

[0178] 120 polarizer

[0179] 130 analyzer

[0180] 140 magnets

Claims

1. A paramagnetic garnet-type transparent ceramic, which is a sintered body of a composite oxide represented by the following formula (1), characterized in that, As a sintering aid, it contains more than 0% by mass and less than 0.1% by mass of SiO2, has an average sintered particle size of more than 5 μm, a total light transmittance of more than 84.0% at a wavelength of 1064 nm with an optical path length of 25 mm, and forward scattering of less than 0.5%. Furthermore, it has a total light transmittance of more than 84.0% at a wavelength of 1300 nm with an optical path length of 25 mm, and forward scattering of less than 0.5%. (Tb 1-x-y Y x Sc y )3(Al 1-z Sc z )5O 12 (1) In the formula, 0.05≤x≤0.4, 0≤y<0.004, 0.6≤1-xy<0.95, 0≤z<0.004, and 0.001<y+z<0.

005.

2. The paramagnetic garnet-type transparent ceramic according to claim 1, wherein, The Feld constant for a wavelength of 1064 nm is 32 rad / (T). (m) or more.

3. The paramagnetic garnet-type transparent ceramic according to claim 1 or 2, wherein, When a 1064nm wavelength laser is incident on a surface with an optical path length of 25mm, the extinction ratio within the entire surface of the optically effective diameter is above 42dB.

4. The paramagnetic garnet-type transparent ceramic according to claim 1 or 2, wherein, When a 1064nm laser with an optical path length of 25mm is incident with a beam diameter of 1.6mm and an incident power of 100W, the change in the beam diameter is less than 10%.

5. The paramagnetic garnet-type transparent ceramic according to claim 1 or 2, having a thermal conductivity of 4.8 W / (m²). K) and above.

6. A magneto-optical material comprising a paramagnetic garnet-type transparent ceramic according to any one of claims 1 to 5.

7. A magneto-optical device comprising the magneto-optical material according to claim 6.

8. The magneto-optical device according to claim 7, comprising the paramagnetic garnet-type transparent ceramic as a Faraday rotor, wherein the magneto-optical device is an optical isolator with polarizing materials on the front and back of the optical axis of the Faraday rotor, which can be used in the wavelength range of above 0.9 μm and below 1.1 μm.

Citation Information

Patent Citations

  • Measuring method of melted metal temperature in vessel

    JP1981011329A

  • Refrigerator

    JP1984035764A

  • Terbium-aluminum-garnet single crystal and method of manufacturing for the same

    JP2002293693A

  • Manufacturing method of ceramics comprising terbium / aluminum oxide and ceramics comprising terbium / aluminum oxide manufactured by the same

    JP2008007385A

  • Garnet crystal for magnetooptical element

    JP2011213552A